Audiological alterations in resistance to thyroid hormone syndrome: emphasizing lifelong assessment - Alexandre Machado Silva de Oliveira; Viviane Motti; Jessica Casemiro; Pedro Resende Rende; Caio Leônidas Oliveira de Andrade; Luciene da Cruz Fernande; Helton Estrela Ramos (Archives of Endocrinology and Metabolism)
ABSTRACT The aim of this study was to investigate the long-term audiological consequences of resistance to thyroid hormone (RTH) syndrome. The cochlea and inner ear express thyroid hormone receptor beta (THRB) in developmental stages. Hearing loss is frequent in subjects with RTH syndrome; however, the long-term impact of insufficient thyroid hormone action in the auditory system remains unknown. Subjects with RTH from the same family, carrying a THRB gene variant, underwent detailed clinical evaluation and serum biochemistry analysis. The genetic assessment involved sequencing of the THRB gene. Hearing loss assessment included (i) meatoscopy, (ii) audiometric tests using pure tone audiometry, (iii) middle ear evaluation by tympanometry, (iv) transient otoacoustic emissions (TOAE), and (v) computed tomography of the mastoids. Genetic sequencing confirmed the THRB gene alteration (p.M442T) in three family members. All affected subjects had clinical and laboratory RTH features. Notably, the older subject with RTH was affected by a bilateral sensorineural hearing loss pattern affected by high frequencies, and cochlear dysfunction was also presented by TOAE analysis, indicating pronounced hearing loss. Hearing loss represents a significant concern in subjects with RTH, emphasizing the need for continuous and comprehensive audiological assessments. These findings underscore the importance of lifelong monitoring, particularly to assess age-related progression of hearing impairment.